2023
DOI: 10.1186/s12931-023-02344-2
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and long‑term respiratory sequelae after severe COVID-19 pneumonia: nitric oxide diffusion measurement value

Abstract: Introduction There are no published studies assessing the evolution of combined determination of the lung diffusing capacity for both nitric oxide and carbon monoxide (DLNO and DLCO) 12 months after the discharge of patients with COVID-19 pneumonia. Methods Prospective cohort study which included patients who were assessed both 3 and 12 months after an episode of SARS-CoV-2 pneumonia. Their clinical status, health condition, lung function testings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…A total of 2517 studies were identified, of which 43 met the inclusion (N = 8858 patients) ( Figure 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. The majority of studies were from China (14 studies [ 51 , 58 , 59 , 60 , 61 , 64 , 65 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 2517 studies were identified, of which 43 met the inclusion (N = 8858 patients) ( Figure 1 ) [ 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ]. The majority of studies were from China (14 studies [ 51 , 58 , 59 , 60 , 61 , 64 , 65 , …”
Section: Resultsmentioning
confidence: 99%
“…The median age of the patients was 60.3 years (57–63), with 61.5% being males and 37.8% being current/former smokers. Thirty-nine studies [ 47 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 65 , 66 , 67 , 68 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 ] reported outcomes stratified by disease severity; 17 for non-severe disease, 31 for severe disease, and 7 for mixed disease severity ( Table 1 ). The most common comorbidities were hypertension (35.8%), cardiovascular disease, (28%), and obesity (24.9%) ( Supplemental Table S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 46 studies with 8289 participants (3338 PASC and 4951 controls) were included in our pooled analysis (Table 1). 24–69 These included studies were all peer‐reviewed, published between 2020 and 2023; had data from 28 studies in Resp‐PASC, 10 studies in Neuro‐PASC, 5 studies in Cardio‐PASC, 2 studies in gastrointestinal‐PASC and as only 1 study was in Reno‐PASC. Thirty‐four studies were of cohort design, 11 were case control and 1 cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, in our population the parenchymal involvement of CT scans is mild on average (about 10% vs 20% in the study by Barisione et al ). Núñez-Fernández and colleagues also assessed the role of DL NO in COVID-19 survivors, both at 3 and 12 months, showing a reduction in diffusion mainly explained by Dm reduction secondary to the damage and loss of alveolar units [ 11 ]. In their study VC and VA significantly improved over time, while DMCO increased less.…”
Section: Discussionmentioning
confidence: 99%